Increased Risk of Pulmonary Tuberculosis in Patients with Depression: A Cohort Study in Taiwan - Kao-Chi Cheng; Kao-Chi Cheng; Kuan-Fu Liao; Kuan-Fu Liao; Kuan-Fu Liao; Cheng-Li Lin; Cheng-Li Lin; Shih-Wei Lai; Shih-Wei Lai (Frontiers in Psychiatry, 2017)
Background/objectiveTuberculosis (TB) and depression were major public health issues worldwide and the mutual causative relationships between them were not exhaustive. This study was performed to explore the association between depression, comorbidities, and the risk of pulmonary TB in Taiwan.MethodsThe cohort study used the database of the Taiwan National Health Insurance Program. The depression group included 34,765 subjects aged 20–84 years with newly diagnosed depression from 2000 to 2012, and the non-depression group included 138,187 randomly selected subjects without depression. Both depression and non-depression groups were matched with respect to sex, age, and comorbidities. We explored the incidence of pulmonary TB at the end of 2013 in both the groups and used multivariable Cox proportional hazards regression model to explore the hazard ratio (HR) and 95% confidence interval (CI) for the risk of pulmonary TB associated with depression.ResultsThe overall incidence of pulmonary TB was 1.16-fold greater in the depression group than that in the non-depression group (1.52 vs. 1.31 per 1,000 person-years, 95% CI 1.12, 1.21). The multivariable Cox proportional hazards regression analysis revealed that the adjusted HR of pulmonary TB was 1.15 for the depression group (95% CI 1.03, 1.28), compared with the non-depression group.ConclusionDepression is associated with 1.15-fold increased hazard of pulmonary TB in Taiwan.